Chronic pruritus - more than a symptom: a qualitative investigation into patients’ subjective illness perceptions - Bathe, Anja; Weisshaar, Elke; Matterne, Uwe (Journal of advanced nursing, 2013)
bathe a., weisshaar e. & matterne u. (2012) Chronic pruritus - more than a symptom: a qualitative investigation into patients’ subjective illness perceptions. Journal of Advanced Nursing69(2), 316-326. doi: 10.1111/j.1365-2648.2012.06009.x Abstract Aim. This article is a report of a study exploring the subjective illness perceptions of patients with chronic pruritus (>6 weeks). Background. Pruritus is a common symptom of dermatological as well as other conditions. This pervasive symptom has a substantial impact on quality of life. Little is known about how patients with chronic pruritus construct the symptom, what causes they ascribe, consequences they endure, how they control the symptom and experience the healthcare system. Design. A qualitative design taking a constructivist inquiry perspective. Methods. Semi-structured interviews with 16 patients were conducted between September 2008-February 2009 and analysed by qualitative content analysis. Results. Many patients find it very difficult to adequately describe the symptom to others resulting sometimes in bizarre accounts of the symptom that provoke irritation in lay people and health professionals. This irritation frequently leaves the sufferer feeling misunderstood. Patients often feel their burden is not taken seriously by health professionals. This and various other reasons contribute to difficulties in accepting a given diagnosis. This can leave patients unsatisfied with their current health care and the system. They respond with frequent doctor changes and consideration of complementary and alternative therapeutic methods. Conclusion. Assisting patients with chronic pruritus in their efforts to adequately describe the symptom along with unconditional regard and empathy are key factors that can help enhance the provider-patient relationship and subsequent acceptance of a given diagnosis. A stronger emphasis on the perspectives of these patients may also improve the quality of healthcare provision.
First published: 09 May 2012
Gesehen am 12.09.2018